2002
DOI: 10.1056/nejmoa991159
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy during Pregnancy and the Risk of an Adverse Outcome

Abstract: As compared with no antiretroviral therapy or monotherapy, combination therapy for HIV-1 infection in pregnant women is not associated with increased rates of premature delivery or with low birth weight, low Apgar scores, or stillbirth in their infants. The association between combination therapy with protease inhibitors and an increased risk of very low birth weight requires confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(106 citation statements)
references
References 22 publications
4
95
2
3
Order By: Relevance
“…Analyzing the quality of pre-natal assistance and the deliveries in public maternities provided for pregnant women, we identified a reality that is far from what is recommended by the Ministry of Health, showing how fragile the Programa Brasileiro de Redução da TV do HIV (Brazilian Program to Reduce the Transmission of HIV), regarding its organization, management and health service assessment (24) . There were a higher percentage of women who had a normal delivery (39.80%) than in other studies (20.5% to 27.3%) (15,25) . The definition of normal delivery is based on the results of the maternal viral load (less than 1.000 copies/mL), conducted after the 34 th week of pregnancy, and in association with an obstetric evaluation (6) .…”
Section: Debatecontrasting
confidence: 64%
See 1 more Smart Citation
“…Analyzing the quality of pre-natal assistance and the deliveries in public maternities provided for pregnant women, we identified a reality that is far from what is recommended by the Ministry of Health, showing how fragile the Programa Brasileiro de Redução da TV do HIV (Brazilian Program to Reduce the Transmission of HIV), regarding its organization, management and health service assessment (24) . There were a higher percentage of women who had a normal delivery (39.80%) than in other studies (20.5% to 27.3%) (15,25) . The definition of normal delivery is based on the results of the maternal viral load (less than 1.000 copies/mL), conducted after the 34 th week of pregnancy, and in association with an obstetric evaluation (6) .…”
Section: Debatecontrasting
confidence: 64%
“…According to reports from HIV positive women who had seronegative children, we found that they were encouraged to seek assistance during their pregnancy (11) . The study found a percentage of approximately 85% compliance with pre-natal care, lower than what is found in Brazil (12,13) and in the world, with a variation of 90 to 100% (14,15). As for compliance with pre-natal care and childbirth ARV treatment, 82.6% and 77.3% pregnant women had prophylaxis treatment, respectively.…”
Section: Debatementioning
confidence: 62%
“…In some studies that have compared HAART use to ZDV monotherapy, an increased risk of preterm delivery among HAART users has been reported 14, 15. However, Tuomala et al 16. reported on a combined analysis of five prospective cohorts and two randomised controlled trials, and did not find an effect of HAART on preterm delivery, in comparison to ZDV monotherapy (odds ratio 1.08, 95% CI 0.71–1.62).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no significant difference in risk of preterm delivery was observed between ZDV‐containing regimens and non‐ZDV ARV regimens. Among studies that examined LBW as an outcome, two African studies14, 17 found an increased risk of LBW with HAART exposure (either before pregnancy or antenatal exposure), whereas three others16, 18, 19 (two in the USA, one in Latin America and the Caribbean) found no effect. Data from this study indicated an increased risk for LBW among pregnancy outcomes with exposure to ZDV‐containing regimens, compared with non‐ZDV ARV regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Additional measures including selective caesarean or avoidance of breastfeeding are strongly recommended. However, adverse pregnancy outcome have been increasingly reported by several observational studies in HIV‐infected women exposed to HAART 6, 7, 8, 9, 10, 11. Anti‐retrovirals and HIV‐infection have been associated with pre‐eclampsia, stillbirth, pre‐term labour, low birth weight and intrauterine growth restriction (IUGR) 12, 13, 14, 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%